Fala-em-interação e serviço social : ações de sondagem na abertura de atendimento a pessoas em situação de rua - Silva Júnior, Antônio Barboza da (2023)
This research produced audiovisual data and analyzed, with special interest in speech-in-interaction and the occasioned semantics by indexes of affective postures, the daily actions that are naturally revealed in care and provision of social work occurring in a unit linked to the Centro de Referência em Assistência Social - CREAS, located in one of the cities of Grande Vitória. Our choice is justified by the idea that "a corpus of recordings of social services constitutes a very solid empirical basis for the study of Social Work, providing the opening of windows for direct observation of professional practices" (Binet, 2014, our translation), and, therefore, contributing to the training, updating and reflection on practices linked to the role of social workers. Hence, the topic adopted for our study is speech-in-interaction (Sacks; Schegloff; Jefferson, 1974) analyzed through observation of indices (Ginzburg, 1990) of expression of affective (Peräkylä, 2012) postures (Schütz, 1945) in interactions linked to the social service context. The method used is subject to the common treatment policy associated with analytical-conversational work with the implementation of some adaptations. In this sense, the audiovisual data generated were received, segmented and transcribed following an adaptation of the transcription model used by the Grupo Linguagem, Interação e Etnometodologia (GLIE), a convention inspired by Jefferson (1972;1973), Sacks, Schegloff and Jefferson (1974) and Mondada (2018). The processing of participants' images was carried out in accordance with the recommendations of the Conselho de Ética em Pesquisas (CEP). The interpretative work was emically guided, following in a subsidiary way the tradition of research in Conversation Analysis (CA) already credible for the analysis of the mentioned phenomena and, in specific and unprecedented cases, guided by the analysis of the materiality of the data generated, being guided by the corpus of audiovisual recordings from a data-driven perspective (Maynard; Clayman, 2003). With these choices, we contribute to the field of social assistance studies, providing a naturalistic look at some survey practices that occur during two service open